Production efficiency of aquaculture farm Vannamei white shrimp in Chachoengsao province, Thailand: a stochastic frontier analysis - Panya Mankeb; Suneeporn Suwanmaneepong; Harry Jay Cavite; Kanokwan Tammaroopa (International Journal of Entrepreneurship and Small Business, 2025)
Inderscience is a global company, a dynamic leading independent journal publisher disseminates the latest research across the broad fields of science, engineering and technology; management, public and business administration; environment, ecological economics and sustainable development; computing, ICT and internet/web services, and related areas.
Keywords: Fisheries and Aquaculture Studies